The Effect Of Transformational Leadership, Organizational Support, And Job Satisfaction On Performance Through Work Engagement As A Mediation Variable - Hefri Ariyanto, Hepy; Prili Yolanda Ayri, Charina; Setyawan, Agustinus (Universitas Lancang Kuning, 2025)
Purpose of This study used work engagement as a mediating variable to investigate how transformational leadership, job satisfaction, and organizational support affect performance. This study is unusual in that it uses work engagement as a mediating variable to identify a new concept of organizational support, job satisfaction, and transformational leadership on employee performance. The population in this study were Civil Servants (PNS) in the Riau Islands Provincial Government, totaling 4,828 people. The number of samples was 370 people. The results of the study showed that all indicator items had a loading factor value > 0.7 so that all questionnaire statement items were declared valid. In the validity test, the Average Variance Extracted (AVE) value ≥ 0.5 means that the construct is said to be valid. Then in the reliability test, the value of Cronbach's Alpha> 0.7 so that the data is said to be reliable. The coefficient of determination (R2) value of the Performance variable has a contribution of 0.448 (44.8%) and Work Engagement 0.572 (57.2%). The conclusion of this study will contribute by observing and feedback, assistance, and ideas to decision makers regarding how transformational leadership, organisational support, job satisfaction, and employee work engagement will affect employee performance.